The Advancement of Women's Portrayal, Position, and Chance in Three Selected Novels (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
Defining Asian literature is always problematic, whether the terminology covers the literary work written by Asians, about Asian or by Asians about Asian(s). Regarding the issue, the women’s position in defining Asian literature is even more problematic since women are considered secondary to men and cultural dominance themes. This paper aims at giving a contribution to what to add in defining Asian literature through the advancement of women’s portrayal, position, and chance in three different female writers. The objects of the review are Ami Tan’s The Joy Luck Club (1989), Ayu Utami’s Saman published in 1998 and translated by Pamela Allen in 2005, Balzac’s My Journey from Paris to Java (2010). This study found that there is an advancement in the women’s portrayal, position, and chance in Asia which are reflected in the three literary works. This advancement confirms the significance of women in representing Asia in the literary works as well as becoming its distinctiveness.